Analisis Yuridis Terhadap Alasan Penemuan Novum Palsu Sebagai Dasar Peninjauan Kembali Kedua dalam Perkara Perdata - Manaqib, Ulil (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2019)
This article discusses the juridical analysis of the reasons for the discovery of a fake novum as the basis of a second review in a civil case. This study aims to answer the question of how are the reasons for the discovery of a fake novum as the basis for a second review in a civil case? and how are the legal analysis of a reason for the discovery of a fake novum as a the basis for a second review in a civil case. The reason for receiving the second review in the civil case is based on the discovery of a novum which was declared false by the Criminal Judge of the Bandung District Court that has inkracht, is a reason that falls within the criteria of Article 67 letter (a) which reads: “If the decision is based on a lie or a ruse the opposing party that is known after the case has been decided or based on evidence which is later declared to be false by the criminal judge”, is not classified as a reason for finding novum or the reason there are two conflicting judicial decisions. Secondly, the second review in the pedata and criminal case is only limited to the reason that there are two Judicial Decisions that are interrelated with one another (SEMA Number 10 Year 2009), so in addition to these reasons, the Supreme Court has never issued a policy related to the second mechanism Judicial Review, including on the grounds that a novum has been legally and convincingly found false by a public court. [Artikel ini membahas tentang analisis yuridis terhadap alasan penemuan novum palsu sebagai dasar Peninjauan Kembali kedua dalam perkara perdata, yang bertujuan menjawab pertanyaan tentang bagaimana alasan penemuan novum palsu sebagai dasar Peninjauan kembali kedua dalam perkara Perdata dan bagaimana analisis yuridis terhadap alasan penemuan novum palsu sebagai dasar Peninjauan Kembali kedua dalam perkara perdata. Alasan diterimanya Peninjauan Kembali kedua dalam perkara Perdata didasarkan pada penemuan novum yang dinyatakan palsu oleh hakim Pidana Pengadilan Negeri Bandung yang telah inkracht, merupakan alasan yang masuk dalam kriteria Pasal 67 huruf (a) yang berbunyi: “apabila putusan didasarkan pada suatu kebohongan atau tipu muslihat pihak lawan yang diketahui setelah perkaranya diputus atau didasarkan pada bukti-bukti yang kemudian oleh hakim pidana dinyatakan palsu”, bukan tergolong pada alasan telah ditemukannya novum atau alasan ada dua putusan badan peradilan yang saling bertentangan. Kedua, Peninjauan Kembali kedua dalam perkara Pedata maupun Pidana hanya terbatas pada alasan ada dua putusan Peninjauan Kembali yang antara satu dan lainnya saling berkelindan (SEMA Nomor 10 Tahun 2009), sehingga selain alasan tersebut Mahkamah Agung belum pernah mengeluarkan kebijakan terkait mekanisme Peninjauan Kembali ke-2, termasuk dengan alasan telah ditemukannya novum yang secara sah dan menyakinkan dinyatakan palsu oleh pengadilan umum.]